2019
DOI: 10.1080/14763141.2019.1671485
|View full text |Cite
|
Sign up to set email alerts
|

How do elite artistic swimmers generate fluid forces by hand during sculling motions?

Abstract: The purpose of this study was to clarify how elite artistic (synchronised) swimmers generate fluid forces with their hands during two kinds of sculling motions: flat sculling in the back-layout position and support sculling in the vertical position. We used the pressuredistribution measuring method to estimate unsteady fluid forces acting on the hand during sculling motions performed by seven elite artistic swimmers. In addition, we simultaneously analysed sculling motions using three dimensional-direct linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In wind-tunnel experiment using a hand model (under steady conditions), it has been reported that an attack angle of about 40° maximises the propulsive lift component (Schleihauf, 1979). Moreover, in a previous study investigating the hand sculling of world-class artistic swimmers using the PDA method (i.e., under unsteady conditions), the peak propulsive force (27.47 ± 7.25 N) was observed when the attack angle was about 20-50° (Homma, Okamoto & Takagi, 2019). The attack angle during sculling affects the 14 pressure fluctuation around the hand (especially the leading part) and the resulting pressure difference induces the generation of unsteady fluid force (including propulsive force) (Homma, Kawai & Takagi, 2016;Takagi et al, 2014).…”
Section: Resultsmentioning
confidence: 95%
“…In wind-tunnel experiment using a hand model (under steady conditions), it has been reported that an attack angle of about 40° maximises the propulsive lift component (Schleihauf, 1979). Moreover, in a previous study investigating the hand sculling of world-class artistic swimmers using the PDA method (i.e., under unsteady conditions), the peak propulsive force (27.47 ± 7.25 N) was observed when the attack angle was about 20-50° (Homma, Okamoto & Takagi, 2019). The attack angle during sculling affects the 14 pressure fluctuation around the hand (especially the leading part) and the resulting pressure difference induces the generation of unsteady fluid force (including propulsive force) (Homma, Kawai & Takagi, 2016;Takagi et al, 2014).…”
Section: Resultsmentioning
confidence: 95%
“…Because sculling movements produce vertical thrust, they help athletes stay in a stable position in the water. As a result of the study, it was understood that the athletes needed advanced sculling movement techniques (Homma et al, 2019). Since movement transitions are important in all competitions of artistic swimming, it has been stated that it is beneficial to study those with high difficulty levels in training programs.…”
Section: Discussionmentioning
confidence: 99%
“…The Through understanding the synchronized swimming water sensation exercises, applicable training methods are borrowed and adapted according to the specific conditions of the specialized class students, appropriately reducing the difficulty level to ensure that students can complete the training as required [5] . Part of the exercises that can be applied are shown in Table 1.…”
Section: Methods Of Synchronized Swimming Water Sensation Practicementioning
confidence: 99%